Réponses

  • Omnes
  • Modérateur confirmé
2014-02-08T22:23:40+01:00
Salut,

 \frac{3- \frac{15}{9} }{ \frac{5}{12} } =  \frac{ \frac{18-15}{9} }{ \frac{5}{12} } =  \frac{ \frac{3}{9} }{ \frac{5}{12}} =  \frac{ \frac{1}{3} }{ \frac{5}{12} } =  \frac{1}{3} *  \frac{12}{5} = \frac{12}{15} =  \frac{4}{5} 


Bonne soirée !
d'accord merci
A = 3 - 15/9 : 5/12
A = 3 - 15/9 x 12/5
A = 3 - 180/45
A = 135/45 - 180/45
A = 3-4
A = -1
comme sa c bon
A = 3 - 15/9 : 5/12
A = 3 - 15/9 x 12/5
A = 3 - 180/45
A = 3-4
A = -1
Comme ça, c'est suffisant
Meilleure réponse !
2014-02-08T22:38:39+01:00
A = 3 - 15/9 : 5/12
A = 3 - 15/9 x 12/5
A = 3 - 180/45
A = 3 x 45 / 1 x 45 - 180/45
A = 135/45 - 180/45
A = 45/45
A = 1


15/9 * 12/5 peut se simplifier et c'est égal à 4
et 3-4 = -1